2018
DOI: 10.1111/trf.15056
|View full text |Cite
|
Sign up to set email alerts
|

The role of pathogen‐reduced platelet transfusions on HLA alloimmunization in hemato‐oncological patients

Abstract: BACKGROUND: Platelet transfusions can induce alloimmunization against HLA antigens. The use of pathogen-reduced platelet concentrates (PCs) was suggested to reduce HLA alloimmunization and concomitant transfusion refractoriness. METHODS:This study investigated HLA alloimmunization in available samples from 448 hematooncological patients who were randomized for the Pathogen Reduction Evaluation and Predictive Analytical Rating Score (PREPAReS) trial to receive either untreated or pathogen-reduced PCs (Mirasol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…The latter possibility was largely not predicted based on in vitro studies (Jackman et al , ), in vivo animal transfusion models (Muench et al , ; Slichter et al , ) and early RCTs (van Rhenen et al , ; McCullough et al , ; Mirasol Clinical Evaluation Study Group, ). More recently, insufficient statistical power prevented the collection of unequivocal evidence on PRT effect on HLA alloimmunization from one study testing samples from recipients of intercept and Mirasol‐treated platelets enrolled in the Italian Platelet Technology Assessment Study (IPTAS) RCT (Norris et al , ), whereas investigators using a larger set of samples from recipients of Mirasol‐treated platelets enrolled in the Pathogen Reduction Evaluation and Predictive Analytical Rating Score (PREPAReS) RCT reported the conclusion that their data ‘clearly indicate that Mirasol pathogen inactivation does not prevent HLA Class I or II alloimmunization after platelet transfusions’ (Saris et al , ). An elegant editorial with a self‐explanatory title that was published shortly after the latter study discusses the available, partially conflicting data and calls for additional, larger studies able to provide conclusive evidence on this issue (Stolla, ).…”
Section: Plateletsmentioning
confidence: 99%
“…The latter possibility was largely not predicted based on in vitro studies (Jackman et al , ), in vivo animal transfusion models (Muench et al , ; Slichter et al , ) and early RCTs (van Rhenen et al , ; McCullough et al , ; Mirasol Clinical Evaluation Study Group, ). More recently, insufficient statistical power prevented the collection of unequivocal evidence on PRT effect on HLA alloimmunization from one study testing samples from recipients of intercept and Mirasol‐treated platelets enrolled in the Italian Platelet Technology Assessment Study (IPTAS) RCT (Norris et al , ), whereas investigators using a larger set of samples from recipients of Mirasol‐treated platelets enrolled in the Pathogen Reduction Evaluation and Predictive Analytical Rating Score (PREPAReS) RCT reported the conclusion that their data ‘clearly indicate that Mirasol pathogen inactivation does not prevent HLA Class I or II alloimmunization after platelet transfusions’ (Saris et al , ). An elegant editorial with a self‐explanatory title that was published shortly after the latter study discusses the available, partially conflicting data and calls for additional, larger studies able to provide conclusive evidence on this issue (Stolla, ).…”
Section: Plateletsmentioning
confidence: 99%
“…14 Practically, however, most leukoreduced units produced on both sides of the Atlantic contain well below these limits. Arguing against a role of WBCs in this setting is another puzzling finding by Saris et al The authors found an increase in HLA Class I antibodies but a contradictory protection from HLA Class II alloimmunization with Mirasol treatment. A possible cellular explanation of this finding is given by the authors themselves: Because WBCs express both HLA Class I and II, but platelets express only Class I antigens, the authors speculate that PRT could protect from WBC alloimmunization, but platelets, which express only HLA Class I, could escape this protective effect.…”
mentioning
confidence: 99%
“…In a recent issue of TRANSFUSION , Saris et al presented a subanalysis of the PREPAReS trial to address this question. This trial was a prospective, randomized controlled trial with a noninferiority endpoint comparing pathogen‐reduced platelets using the Mirasol technology to conventional untreated platelet units .…”
mentioning
confidence: 99%
See 2 more Smart Citations